Analysis of Risk Factors for Refractive Errors in Khairun University Medical Students in 2023 - Armaijn, Liasari; Do Toka, Wahyunita; Maulany Abdullah, Rizka (Alami Journal (Alauddin Islamic Medical) Journal, 2024)
Refractive error is a condition in which the optical system of the eye blocks the entry of light at one focal point on the retina, resulting in decreased vision. Risk factors such as genetics, environment, and gender can lead to refractive errors. This study aims to analyze the risk factors of refractive errors in Khairun University Medical students. This research is an analytic study with a cross-sectional approach conducted at the Faculty of Medicine, Khairun University, from March to April 2023. Sample collection using total sampling technique, then univariate and bivariate analysis using chi-square test. The instruments in this study used questionnaires and Snellen charts. The results showed that most ages were 17-18 years, as many as 55 people (59.1%), with the female gender as many as 86 people (92.5%). Based on the chi-square test, the results showed a significant relationship between reading distance and refractive errors p=0,043 Prevalence Risk (PR) CI 95% 2,400 (1,022-5,635) and duration of using mobile phones on the incidence of refractive errors p=0.047 PR CI 95% 2,437 (1,100-5,935). It can be concluded that among all the risk factors analyzed, reading distance and the duration of mobile phone use were found to be risk factors for reactive error in medical students.